The GIS book - Korte, George (Onword Press, 2001)
Discover what a geographic information system (GIS) is, how it applies to a variety of professions, and the benefits of using GIS for a variety of applications. Praised through four highly successful editions, The GIS Book, 5th Edition now features hands-on exercises enabling readers to use free GIS software and data downloaded over the Internet to gain a first-hand understanding of the power of GIS technology today. New chapters on GIS data sources, data quality, plus managing and maintaining a GIS database have also been added to educate those new to GIS about one of the most important aspects of implementing any GIS project